2020
DOI: 10.1177/0361198120919118
|View full text |Cite
|
Sign up to set email alerts
|

Mobile Application Development and Testing for Work Zone Activity Real-Time Data Collection

Abstract: Work zones are prevalent in the United States as the infrastructure is increasingly in need of maintenance. Lack of reliable data is one of the main obstacles in work zone research. Reliability suffers because of underreporting of crashes and inclusion in the analysis of irrelevant activities that are not attributable to work zones. In addition, the work zone environment is very dynamic, resulting in differing reasons for crashes. These are barriers to gaining an accurate understanding of safety in work zones.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 5 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…The Bluetooth and Ultra-Wide Band technologies provided limited range [48,33] making them only applicable for short-range applications like sign detection. The cellular internet communication allowed for a network-wide coverage but with limited latency [77]; however, as stated previously the recent 5G cellular technology promises for low latency and deserves further testing at WZ sites. The one well researched technology at WZs that provided a trade-off between coverage and latency is the DSRC as explored by Maitipe et al [62,63], Zaman et al [75], and Ibrahim et al [76].…”
Section: Cav Communication At Wzs: Existing Literaturementioning
confidence: 98%
“…The Bluetooth and Ultra-Wide Band technologies provided limited range [48,33] making them only applicable for short-range applications like sign detection. The cellular internet communication allowed for a network-wide coverage but with limited latency [77]; however, as stated previously the recent 5G cellular technology promises for low latency and deserves further testing at WZ sites. The one well researched technology at WZs that provided a trade-off between coverage and latency is the DSRC as explored by Maitipe et al [62,63], Zaman et al [75], and Ibrahim et al [76].…”
Section: Cav Communication At Wzs: Existing Literaturementioning
confidence: 98%
“…When a work zone is detected, the smartphone vibrates to alert users, and the app then broadcasts an audible message to them (Liao, 2014). Azadi et al (2020) developed and deployed a work zone application for collecting, reporting, and storing real-time work-zone activity information. The study indicated that the precision of sensors such as GPS was within appreciable accuracy of work zone geolocation.…”
Section: Related Studiesmentioning
confidence: 99%